Postoperative outcomes in total hip arthroplasty following femoral head avascular necrosis in HIV-positive patients. - Manzotti, Alfonso; Larghi, Marco; Placenza, Emanuele; Susini, Francesca; Grassi, Miriam (Acta Biomedica Atenei Parmensis, 2021)
Background: Few clinical studies have been published reporting the clinical outcomes of total hip replacement (THA) in HIV-positive patients affected by femoral head avascular necrosis (AVN) often with controversial results and often without any correlation with the immunological patient status. Our study aim is to retrospectively review the outcome of a HIV-positive patient series. Material and Methods: 24 THAs perfomed between 2007 and  2017 were assessed in the study. All patients have been classified with Charlson Comorbidity Index (CCI) and the CDC (Center for Disease Control and Prevention) HIV classification.  At the latest follow-up each patient have been evaluated using Harris Hip Score (HHS), WOMAC score, a numerical pain rating scale (NRS) and procedure-related complications were collected. Results:At a mean mean follow up of 96,41 months the mean WOMAC score was 91,66  and the mean Harris Hip Score was 86,77 with  excellent results in 18 hips, good in 1 and poor in the 5. Post-operative complications were reported in 7 hips, 3 patients developed a periprosthetic joint infection (PJI) in patients with low CD4+ count and history of intravenous drug consumption. Conclusion: We registered a good outcome in HIV patient with femoral head AVN treated with Total Hip replacement. However, we reported a significant increase in complications and revision rate especially referred to PJI, in patient with history of intravenous drug consumption and low CD4+ count. The authors advocate further prospective multicentric studies with larger population in the future. (www.actabiomedica.it)